Solution focused therapy untuk memperbaiki pola komunikasi suami-istri - Eka Hertisyahrani (Universitas Muhammadiyah Malang, 2023)
Ineffective communication within a family is a problem that often occurs and requires immediate treatment so as not to cause more severe problems. The lack of effective communication in this family was initially complained about by the wife, who complained about the changes in behavior experienced by her husband since he started working. Changes in behavior around being reluctant to communicate his disapproval and acting indifferent to his wife's feelings make him feel uncomfortable. This non-assertive behavior forms an indirect or indirect communication pattern that results in disharmony in household relations. Observation, interviews, and the Couple Communication Satisfaction Scale (CCSS) are the assessments carried out to explore the problem. The intervention used is solution-focused therapy (SFT); the implementation procedure consists of 6 sessions to improve communication patterns between husband and wife. SFT is proven to be able to improve communication patterns that exist between husband and wife. These changes in more positive communication between couples mean that interactions within the family are better than before and that family members are spending more time together than before. Keyword : Solution-focused therapy, communication, couple communication satisfaction Abstrak Komunikasi yang tidak efektif dalam keluarga merupakan masalah yang sering terjadi dan memerlukan penanganan segera agar tidak menimbulkan masalah yang lebih berat. Kurangnya komunikasi yang efektif dalam keluarga ini awalnya dikeluhkan oleh istri yang mengeluhkan perubahan perilaku yang dialami suaminya sejak mulai bekerja. Perubahan perilaku seputar keengganan untuk mengomunikasikan ketidaksetujuannya dan bersikap acuh tak acuh terhadap perasaan istrinya membuatnya merasa tidak nyaman. Perilaku tidak asertif ini membentuk pola komunikasi tidak langsung atau tidak langsung yang mengakibatkan ketidakharmonisan dalam hubungan rumah tangga. Observasi, wawancara, dan Couple Communication Satisfaction Scale (CCSS) merupakan penilaian yang dilakukan untuk menggali permasalahan. Intervensi yang digunakan adalah solution-focused therapy (SFT); Prosedur pelaksanaannya terdiri dari 6 sesi untuk memperbaiki pola komunikasi antara suami dan istri. SFT terbukti mampu memperbaiki pola komunikasi yang terjalin antara suami istri. Perubahan dalam komunikasi yang lebih positif antara pasangan ini berarti bahwa interaksi dalam keluarga menjadi lebih baik dari sebelumnya dan anggota keluarga menghabiskan lebih banyak waktu bersama daripada sebelumnya. Kata kunci: Solution-focused therapy, komunikasi, couple communication satisfaction